Influence of cultural values and hierarchical social norms on buying counterfeits online: a 17-country study - Kononova, Anastasia; Huddleston, Patricia; Moldagaliyeva, Moldir; Lee, Heijin; Alhabash, Saleem (Frontiers in Psychology, 2024)
Introduction As a globally prevalent phenomenon, buying counterfeit products harms consumers, economies, societies, governments, and the environment. The study examined the hierarchy of injunctive normative influence (personal vs. societal) on counterfeit purchase intentions and trends in non-deceptive (known) counterfeit purchase behavior. The current research expands the hierarchical norms approach by examining how the cultural values of power distance and individualism–collectivism predict injunctive normative perceptions and counterfeit buying intention and behavior. Methods A cross-sectional survey (N = 13,053) of consumers from 17 nations, administered in seven languages, explored cross-country differences in perceived social norms about buying counterfeits. Results The findings of multilevel moderated mediation analyses showed that personal injunctive norms (perceived acceptance of buying counterfeits by close friends) mediated the relationship between societal injunctive norms (perceived acceptance for buying counterfeits by peers in the same country) and the outcome variables. Selected paths of the mediation model were moderated by the two cultural dimensions. Discussion Theoretical implications are discussed within the context of cultural orientations’ and social norms’ roles in informing risky behavior, and practically, within the context of awareness-raising and behavior-change interventions.